Three cheers, secret seven - Blyton, Enid (Hodder Children's London, 2002)
When Peter and Jack go looking for their lost model aeroplane in an old abandoned house, they find a lit fire in one of the rooms. So who is living there, and why? Looks like the Secret Seven have another interesting case to solve..